A formação profissional do engenheiro agrônomo frente ao desenvolvimento rural sustentável - Dettmer , Tatiana Lagemann (2017)
Education plays an important role in development and growth of the country. From the National Curricular Guidelines (DCN), published in 2006, Higher Education institutions become more autonomous in the elaboration of the Pedagogical Political Projects (PPP) of their courses. The objective of this research work was to understand how educational institutions contextualize the theme of sustainable rural development in their PPPs, as well as the professionals and entrepreneurs view in the agricultural area on the professional training of the Agronomist. This research was carried out through dialectical and phenomenological methods, besides the Survey. It is divided into two chapters. The first one describes an analysis of Agronomy Courses in public and private universities of the State of Paraná over the perspective of sustainable rural development, studying their PPPs. The second chapter analyses the agronomist professional profile and what the job market demands for this professional, in order to identify if the universities are following the needs of the job market as well as if they are working in order to abide the current legislation concerning to Agronomy Courses.